Reshaping perioperative nursing practice to get the job done: A constructivist grounded theory study - Sharon Bingham; Kenneth Walsh; Karen Ford (Journal of Perioperative Nursing)
An estimated 234 million operations are performed in hospitals each year and complications of surgery are common and often preventable. The rates of complications vary between studies with reports of perioperative death rates of between 0.4 and 0.8 per cent and rates of complications between 3 and 17 per cent. Adverse events can lead to patient disability, death, or increased length of stay, imposing a significant burden on the health care system, patients and their families.